Estudio Teórico de la Influencia del Uso de Mezclas de Biodiesel de Aceite de Palma con JET a-1 en Motores a Reacción - Mónico Muñoz, Luisa Fernanda; Sandoval Sotelo, Juan José; Rodríguez Chaparro, Andrés Felipe (Ingeniería, 2017)
Context: like many others, today the aeronautical industry has been forced to implement methods to mitigate the damage produced to the environment due to the emission of polluting gases and in doing so, confront the problem of global warming. In this context, research on the use of alternative fuels is of paramount importance, in particular the study of engine performance when using blends of Colombian Biodiesel based on palm oil with Jet A1. Method: as a starting point, we made a review of the state of the art so as to select which engine to study and then the alternative fuels to be used. Simultaneously, Colombian biodiesel based on palm oil was selected, as it has been shown to be a fuel with good performance when it is blended in percentages of 10%, 20% and 50%. Each of the blends were tested in the laboratory to obtain their viscosity, density and calorific values. A spreadsheet program was developed to conduct the analysis, which contemplated the physical properties of mixtures and engine parameters, as well as emissions of nitrous oxides (NOx), atomization and combustion produced by the use of mixtures. The results were compared against those of the Gasturbine simulation software Results: CFM 56-5B was chosen as the appropriate engine for the study, because it is currently the most used in the Colombian aeronautical industry. On the other hand, none of the alternative fuel blends generates the same engine performance when using Jet A1. The blends E10 and E20 have a similar behavior, with the novelty of generating less amount of NOx emissions and improving the atomization of the fuel. Conclusions: When the engine’s performance with conventional fuel is comparing with Biodiesel mixtures, a decrease of the thrust is produced as the percentage of Biodiesel in the mixture increases. Because the mixtures of alternative fuel have a lower calorific value fuel consumption in these cases is always greater. However, when comparing the NOx levels produced, a decrease of this pollutant is observed when using Biodiesel blends. It is worth noting that it is of great interest for future work to evaluate other pollutant emissions and, in turn, the behavior of other types of Biodiesel in jet engines. Language: Spanish.